2021
DOI: 10.1177/21582440211005454
|View full text |Cite
|
Sign up to set email alerts
|

Disciplinary Recognized Self-Presence: Self-Mention Used With Hedges and Boosters in PhD Students’ Research Writing

Abstract: Despite the existing extensive research on stance markers such as hedges, boosters, and self-mention in academic writing, few studies, however, examined the co-occurrence of these stance markers to help authors project their identities in writing. In this study, we examine how self-mention with boosters and hedges are used by writers of different groups to manifest authorial presence and what functions they realize in research writing. Two self-compiled corpora were constructed to compare the discursive practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…In Ex 12, the MS participant tends to be more authoritative in his status update using the obligation marker "must" which emphasizes the expression of authority by a person with power. This is in line with the study of Wang & Zeng (2021), who conclude that participants use first-person pronouns in collocation with other lexical devices, mainly hedges or boosters. They suggest that this can fine-tune the role of authorial commitment in a text.…”
Section: ‫بحٕث‬ ‫يجهة‬supporting
confidence: 91%
“…In Ex 12, the MS participant tends to be more authoritative in his status update using the obligation marker "must" which emphasizes the expression of authority by a person with power. This is in line with the study of Wang & Zeng (2021), who conclude that participants use first-person pronouns in collocation with other lexical devices, mainly hedges or boosters. They suggest that this can fine-tune the role of authorial commitment in a text.…”
Section: ‫بحٕث‬ ‫يجهة‬supporting
confidence: 91%
“…In fact, it was also found that the discussion section of the thesis had a substance that deviated from the research results (J. Wang & Zeng, 2021) . This fact can happen because many students actually do not understand correctly the nature of the discussion section of the thesis.…”
Section: Introductionmentioning
confidence: 95%
“…He also emphasizes that arguments in soft knowledge domains are different from those of hard science domains due to the nature of these sciences. As Wang and Zeng (2021) contend, the use of first-person pronouns varies based on the discursive rules of each discipline. In a recent study, Hyland and Jiang (2018) found that self-mention pronouns have increased dramatically in sociology, biology, and electrical engineering over the last 50 years but have decreased in applied linguistics.…”
Section: Review Of Related Studiesmentioning
confidence: 99%